2013
DOI: 10.3109/19396368.2013.809173
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of sperm retrieival on testis and epididymis: an experimental study using Wistar albino rats

Abstract: The aim of this study was to analyze pathophysiological changes after testicular sperm aspiration (TESA) and microsurgical epididymal sperm aspiration (MESA) procedures. Twenty four mature male Wistar albino rats with a proven breeding history, weighing approximately 200-250 gm were used for the study. Animals were randomly divided into four groups (n = 6), i.e., control, sham-control, unilateral TESA, and MESA. Using a 22G needle, the aspiration procedures were done in testis or caudal epididymis. At the end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Sperm cells were present in minor to moderate levels in the epididymis' tubular lumen. These results substantially support the previous findings of Prithiviraj et al [33]. After sperm extraction, men's serum samples contained ASAs of the IgG class, according to Wood et al [21].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Sperm cells were present in minor to moderate levels in the epididymis' tubular lumen. These results substantially support the previous findings of Prithiviraj et al [33]. After sperm extraction, men's serum samples contained ASAs of the IgG class, according to Wood et al [21].…”
Section: Discussionsupporting
confidence: 91%
“…Testicular sperm aspiration has been utilized to extract sperm from humans and several animal species, including rams, and rat models [18][19][20]. Prithiviraj et al [33] and Shufaro et al [34] both demonstrated that biopsies significantly elevate and produce ASAs. As a result, TSA was utilized in the current study as a rat model for ASAs production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The damage caused by this is seen clinically in the finding that in 11% of cases where sperm were present during the first TESA procedure, no sperm were found during a repeat procedure [13] . A study on the rat testis showed that TESA led to high antibody titres, increased germ cell apoptosis, and extensive fibrosis of the parenchyma [26] . Thus, TESA is inefficient (low SRR) and traumatic, and hence is not recommended even though it is widely used by gynaecologists.…”
Section: Discussionmentioning
confidence: 99%